Single Crystal EPR of the Mixed-Ligand Complex of Copper(II) with l -Glutamic Acid and 1,10-Phenanthroline: A Study on the Narrowing of the Hyperfine Structure by Exchange - Neuman, Nicolás Ignacio (2012)
We report an EPR study at X- and Q-bands of polycrystalline and single crystal samples of the mixed copper(II) complex with L-glutamic acid (glu) and 1,10-phenantroline (phen), [Cu(glu)(phen)(H2O)]+ NO3 −·2(H2O). The polycrystalline sample spectrum at Q-band showed well resolved g∥ and g⊥ features and partially solved hyperfine structure at g∥, typical for weakly exchange coupled systems. This is confirmed from the angular variation of the EPR spectra which shows for certain magnetic field orientations a partially solved hyperfine structure characteristic of weak exchange, whereas a single Lorentzian line corresponding to strong exchange is observed for others. Analysis and simulation of the single crystal EPR spectra were performed using the random frequency modulation model of Anderson. Numerical simulations of the angular variation of the EPR spectra showed that the narrowing of the hyperfine structure is due to an exchange-mediated mechanism in which transitions between any pair of lines are equally likely. The exchange interaction responsible for this process is mediated by hydrophobic interactions between two phen molecules and a mixed chemical path of the type CuA−OapH···O− C−Oeq−CuB, for which we evaluated an average isotropic exchange parameter |J| ≈ 25 × 10−4 cm−1.